Reproduction of Meloidogyne arenaria race 2 on Flue-cured tobacco possessing resistance genes Rk1 and/or Rk2 - Adamo, Noah (J Nematol, 2021)
Resistance to Meloidogyne incognita races 1 and 3 and race 1 of M. arenaria is imparted to flue-cured tobacco by the gene Rk1. Meloidogyne arenaria race 2 is not controlled by Rk1 and has become prevalent in Virginia. A second form of resistance effective against M. javanica, Rk2, is also increasingly available commercially. Greenhouse and field trials including a root-knot susceptible cultivar, cultivars homozygous for Rk1 or Rk2, and cultivars possessing both genes were conducted in 2018 and 2019 to investigate the effect of Rk1 and/or Rk2 on parasitism and reproduction of M. arenaria race 2. Plants were inoculated with 5,000 M. arenaria race 2 eggs in the greenhouse or infested by a native nematode population in the field. Data were collected after 28 days (greenhouse) or every 3 weeks following transplant until 18 weeks in the field and included root galling index, nematodes present in roots, egg mass numbers, and egg counts; reproductive indices were also calculated. We found that the combination of Rk1 and Rk2 provides greater resistance to M. arenaria race 2 than either gene alone. While the effect of either gene alone was inconsistent, we did observe some significant reductions in galling and reproduction associated with each gene relative to the susceptible control.